Instrument assisted soft tissue mobilization- an emerging trend for soft tissue dysfunction - Tahir Mahmood; Muhammad Hafeez; Muhammad Waqas Ghauri; Abdul Salam (Journal of the Pakistan Medical Association, 2020)
Abstract Musculoskeletal disorders are common conditions involving joints, muscles. Nerves, ligaments and tendons found in the community. These disorders affect the normal activities and causes discomfort. These discomforts are managed by different types of interventions including exercise, acupuncture, soft tissue release and manual therapy as conservative mode of management. Soft tissue release including active release technique, Fascial abrasion, and myofascial release are considered effective for musculoskeletal functions improvement. The advancements and technology improved and Instrument assisted techniques are being used. These different types of instruments including Graston, Ergon, Gua Sha, Hawk Grips, Rock Tapes, FAKTR. These instruments are sensitive in localization, specification and facilitation of the target area with the help of mechanical pressure applied on tissue with movement of specific muscle. Prognosis varies with good outcomes using fewer sessions than others.But it needs proper localization of muscle involved and special training. The advantage considered is that musculoskeletal disorders Continuous...